Sequential MR Images and Radiographs of Epiphyseal Osteomyelitis in the Distal Femur of an Infant - Hitomi Hara; Toshihiro Akisue; Teruya Kawamoto; Masahiro Kurosaka (Case Reports in Radiology)
Magnetic resonance imaging (MRI) plays an important role in the diagnosis of osteomyelitis, especially during the early phase of the disease. The findings of sequential MRIs during the course of treatment in acute osteomyelitis in children have not yet been reported in the literature. We present a case of acute epiphyseal osteomyelitis in the distal femur of an infant. We monitored imaging changes by sequential MRIs and radiographs. MRI was more useful than radiograph for early diagnosis and evaluation of therapeutic response.